1-(1-Benzofuran-2-yl)ethanone O-(2-chlorobenzoyl)oxime - Iskeleli, NO; Kazak, C; Kirilmis, C; Koca, M (Int Union Crystallography, 2005)
The title compound, C17H12ClNO3, displays the characteristic features of benzofuran derivatives. The molecule is not planar. Intermolecular C - H center dot center dot center dot O interactions help to stabilize the structure.